Development of a Church Asset Management System with an Agile Approach in the Pasundan Christian Church - Bias Yulisa Geni; Edwar Christoper Pendjol (Ali Institute or Research and Publication, 2025)
The Manual asset management still used at the Pasundan Christian Church Kampung Sawah Congregation has led to various challenges, including recording errors, data duplication, and limited capabilities for real-time reporting and monitoring. This study aims to design and develop a web-based asset management information system to enhance accuracy, efficiency, and transparency in church asset administration. The system development process adopts the Agile methodology with a Scrum approach, enabling iterative and collaborative development between the development team and stakeholders. The Scrum method includes stages such as User Story, Product Backlog, Sprint, Sprint Backlog, and Daily Scrum. The system is web-based, developed using PHP as the programming language and MySQL as the database. The framework used is PHP. The system comprises 14 core features, including asset recording, modification, deletion, search, printing, and management of asset borrowing and returning. Three types of users are identified: the Household Commission as the primary administrator, the Church Council as borrowers, and the Pastor as a passive user. Testing was conducted using the black-box method to evaluate the performance of each feature. The results show that all 14 features (100%) functioned as expected. Overall, the system successfully improves reliability and transparency in asset management and supports a more organized and efficient organizational service.